Intimate Partner Violence among Scheduled Caste Women in India: A Cross-sectional Study - Chowdhury, Sourav (Victims & offenders, 2024)
Scheduled Caste (SC) women, one of the most oppressed and neglected groups in India, have the highest prevalence of intimate partner violence (IPV), yet no study has analyzed correlates of IPV within this group, or analyzed them using nationally representative data. This study is an attempt to fill this gap. Information on 11,076 married SC women from the National Family Health Survey-4 was analyzed. Cross-sectional study design was followed. Binary logistic regression was applied to examine the factors associated with IPV. About 40% of married SC women in India suffered physical, mental, or sexual violence from their husbands. Alcohol consumption by husband (OR = 2.99, 95% CI = 2.62–3.41), employment status (OR = 1.26, 95% CI = 1.07–1.48), parity especially having 4 or more children (OR = 2.36, 95% CI = 1.82–3.06; OR = 2.10, 95% CI = 1.61–2.73) were associated with higher odds of IPV. Women from southern, eastern, and central regions of India were more likely to experience IPV. We conclude that there is a need to recognize the diverse experiences of vulnerable subgroups within SC women and undertake suitably designed targeted interventions to lower the high levels of IPV prevalent among these women.